Gut microbiota-driven dysbiosis of the SCFA-immune axis in pediatric allergic rhinitis-constipation comorbidity: mechanisms and synbiotic remodeling - Yang, WeiKeng; Zhang, Xiaojiao; Wu, Bin; Ni, Binyu; Lin, Hongbin; Huang, Congfu (Frontiers in Immunology, 2025)
BackgroundThe coexistence of allergic rhinitis (AR) and functional constipation (FC) in children reflects complex gut–immune interactions; however, the contribution of microbiota-derived short-chain fatty acids (SCFAs) to immune-metabolic dysregulation remains poorly defined.MethodsFecal microbiota from 57 AR-FC children (aged 0–6 years) and 59 age-matched healthy controls (HC) were profiled using 16S rRNA gene sequencing, and functional pathways were inferred via PICRUSt2. A subset of 13 preschoolers (aged 3–7 years) underwent a 3-month synbiotic intervention (multi-strain probiotics combined with dietary fiber), with paired pre- and post-treatment samples analyzed.ResultsAR-FC subjects exhibited reduced α- diversity (P = 0.003) and depletion of SCFAs-producing taxa (Faecalibacterium prausnitzii: Log2FC = −2.1, P = 0.001; Bacteroides stercoris: Log2FC = −1.8, P = 0.005). Alterations were observed in functional pathways, including upregulated proteasome activity (P = 0.01, potentially linked to antigen processing) and suppressed LPS biosynthesis (P = 0.02, suggestive of impaired innate immunity). Synbiotic administration enriched Faecalibacterium abundance (+54.8%, P < 0.05) and alleviated constipation but reduced Bifidobacterium (−85.2%, P < 0.05), reflecting substrate competition. Following synbiotic intervention, metabolic remodeling was characterized by increased sulfur assimilation (+83.2% sulfate reduction, P = 0.04) and diminished β-lactam resistance (−35.4%, P = 0.03).ConclusionGut dysbiosis in AR-FC comorbidity is associated with disruption of the microbiota–SCFA–immune axis, which may correlate with mucosal barrier defects and a potential bias toward T helper 2 (Th2) polarization. Although synbiotic therapy induced taxonomic shifts and improved gastrointestinal function, our findings highlight the need for strain-specific formulations to achieve comprehensive immune and intestinal restoration.